(untitled) (Oratio Directa, 2023)
Artificial intelligence is a computer-based system increasingly used across digital technologies and capable of transforming global society positively and negatively. This qualitative study uses philosophical analysis and literature review to examine AI's ontological, epistemological, and axiological dimensions. AI is understood ontologically as computer-generated intelligence, epistemologically as a multidisciplinary construction, and axiologically as a double-edged technology. The study concludes that AI must be directed toward improving human life and strengthening Indonesia's civilization.